2021
DOI: 10.3390/coatings11121524
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of NiCr/NiCr-Al2O3/Al2O3 Multilayer Gradient Coatings by Gas Detonation Spraying

Abstract: This paper investigates the influence of the technological parameters of detonation spraying on the phase composition of NiCr- and Al2O3-based coatings. It was determined that the phase composition of Al2O3 coatings during detonation spraying strongly depends on the barrel filling volume with the gas mixture. The acetylene–oxygen mixture, which is the most frequently used fuel in the detonation spraying of powder materials, was used as a fuel gas. To obtain a ceramic layer based on Al2O3, spraying was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A small number of pores and cracks are observed at the interface between the white, curved strips and the gray matrix. In [28,29], it is reported that the coatings obtained by detonation spraying have a wave-like porous structure. EDS analysis along the gradient-structured coating line showed that the light, curved bands consisted mainly of Ti, while the dark regions consisted mainly of Ti and O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of pores and cracks are observed at the interface between the white, curved strips and the gray matrix. In [28,29], it is reported that the coatings obtained by detonation spraying have a wave-like porous structure. EDS analysis along the gradient-structured coating line showed that the light, curved bands consisted mainly of Ti, while the dark regions consisted mainly of Ti and O.…”
Section: Resultsmentioning
confidence: 99%
“…A small number of pores and cracks are observed at the interface between the white, curved strips and the gray matrix. In [28,29], it is reported that the coatings obtained by detonation spraying have a wave-like porous structure. Tribological tests of the coatings obtained under different regimes of detonation spraying were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, WC-Co-Cr coatings can be applied to pipeline valve parts using the HVOF process as a replacement for conventional hard chrome plating to extend the service life of gate valves [1,19]. WC-Co-Cr coatings can also be deposited using various spraying methods such as air plasma spraying (APS), vacuum plasma spraying (VPS), detonation spraying, arc spraying and flame spraying [20][21][22][23][24][25][26]. Among the above methods, the HVOF process is considered to be the most promising method, successfully providing solutions to many issues related to oxidation, wear resistance, hot corrosion and erosion [27].…”
Section: Introductionmentioning
confidence: 99%
“…Detonation spraying is widely used to obtain gradient coatings [23][24][25]. Detonation spraying of gradient coatings is performed by alternating shots from two powder dispensers with diferent powders [22].…”
Section: Introductionmentioning
confidence: 99%
“…Terefore, we developed a method of obtaining composite gradient coatings by varying the spray parameters during spraying, i.e., after a certain number of shots, the technological modes (the barrel flling degree, gas ratio, etc.) change [22][23][24][25]. To implement this method, it is necessary to apply a detonation setup with a single powder dispenser flled with composite powder.…”
Section: Introductionmentioning
confidence: 99%